I am an apple Ako ay isang apol - Chong, Grace D.; Pineda, Lou (Quezon City Lampara Publishing House, Inc., 2013)
"Abet is very sad. he does not want to fly kite anymore. he has just discovered he is an adopted child. But Pedro's balikbayan friend Adora suddenly arrives. Adora has brought a big apple. She says, "I am an apple! A--as in Apple. A--as in adopted. Adora is also an adopted child, but she is the apple of the eye of her adoptive parents. Find out in this story how Abet comes to terms with being an adopted child and what 'apple of the eye' means."
Stories with moral values
Text in English and Filipino.
Don Carlos Palanca memorial awards for literature, third prize, short story for children 2010.
Keywords: Adoption -- Juvenile fiction; Children, Adopted